Mace‐Like Plasmonic Au‐Pd Heterostructures Boost Near‐Infrared Photoimmunotherapy - Yanlin Feng; Xin Ning; Jianlin Wang; Zhaoyang Wen; Fangfang Cao; Qing You; Jianhua Zou; Xin Zhou; Teng Sun; Jimin Cao; Xiaoyuan Chen (Advanced Science, 2023)
Abstract Photoimmunotherapy, with spatiotemporal precision and noninvasive property, has provided a novel targeted therapeutic strategy for highly malignant triple‐negative breast cancer (TNBC). However, their therapeutic effect is severely restricted by the insufficient generation of tumor antigens and the weak activation of immune response, which is caused by the limited tissue penetration of light and complex immunosuppressive microenvironment. To improve the outcomes, herein, mace‐like plasmonic AuPd heterostructures (Au Pd HSs) have been fabricated to boost near‐infrared (NIR) photoimmunotherapy. The plasmonic Au Pd HSs exhibit strong photothermal and photodynamic effects under NIR light irradiation, effectively triggering immunogenic cell death (ICD) to activate the immune response. Meanwhile, the spiky surface of Au Pd HSs can also stimulate the maturation of DCs to present these antigens, amplifying the immune response. Ultimately, combining with anti‐programmed death‐ligand 1 (α‐PD‐L1) will further reverse the immunosuppressive microenvironment and enhance the infiltration of cytotoxic T lymphocytes (CTLs), not only eradicating primary TNBC but also completely inhibiting mimetic metastatic TNBC. Overall, the current study opens a new path for the treatment of TNBC through immunotherapy by integrating nanotopology and plasmonic performance.